2009
DOI: 10.3149/jmh.0801.22
|View full text |Cite
|
Sign up to set email alerts
|

A Marked Man: Female-Perpetrated Intimate Partner Abuse

Abstract: Concepts of intimate partner abuse and violence are shifting, complex, situationally-contingent and multi-faceted. Whilst women's narratives of abuse have provided much-needed, if harrowing, insight into the subjective experience of intimate partner abuse, men's accounts of femaleperpetrated abuse have been slower to emerge, generating much controversy and hostility even in contemporary times. This paper seeks to add to a small, but developing qualitative literature on male victims' accounts of intimate abuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 53 publications
(34 reference statements)
5
76
0
1
Order By: Relevance
“…None of the victims presented severe consequences; despite these findings, several authors referred that men may be seriously injured. 16,20,29,30,33 Intimate partner violence may have psychological negative outcomes in the victims, 20 however, these possible effects were not assessed in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…None of the victims presented severe consequences; despite these findings, several authors referred that men may be seriously injured. 16,20,29,30,33 Intimate partner violence may have psychological negative outcomes in the victims, 20 however, these possible effects were not assessed in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…The majority of these studies focus on the prevalence of male victims of IPV, characterization of the violent episode, including motives and mechanisms of aggression and its consequences for the victim. 15,16,19,20 Some studies compare male victims of IPV with female victims of this type of violence. 10,22,23 The characterization of IPV perpetrated against men is important to better understand this phenomenon and to assess the need to create public policies in order to prevent it.…”
Section: Introductionmentioning
confidence: 99%
“…The marked difference of the structure and form of the abuse narrative reiterates the fact that IPV remains an "unbelievable" or "forbidden" discourse for male victims (Allen-Collinson, 2009a, 2009bMigliaccio, 2002). The findings of this study suggest that a broad questioning technique (e.g., "How are the children?…”
Section: Resultsmentioning
confidence: 99%
“…In the context of this study, it is suggested that the abuse narrative constituted the "forbidden" narrative, which was unbelievable in terms of its content and narrative style but also by the inextricable link between femininity and victimhood (Allen-Collinson, 2009a, 2009b. As highlighted earlier, the abuse narrative was notably difficult to articulate (Plummer, 1995) and directly challenged the men's gendered assumptions of themselves, given that discourses of victimhood and vulnerability are not "known" within a masculinist discourse (Burr, 2008).…”
Section: Journal Of Interpersonal Violencementioning
confidence: 88%
See 1 more Smart Citation